Food Grabbing Behavior Modification Program Using Shaping Techniques with Tablet Media for Autistic Children - Wagino; Prameswari , Aloysia Dian Nimas (Universitas Pendidikan Ganesha, 2023)
Children with autism often have difficulty interacting socially and understanding applicable social norms. Therefore, appropriate behavior modification strategies are needed to help autistic children overcome food-grabbing behavior and learn how to interact better socially. This research aims to use shaping techniques to change the behavior of autistic students who often grab other people's food. This research involves the use of tablet media as a tool to provide intervention. The research subjects in this study were autistic students who tended to snatch other people's food. This research uses the Single Subject Research method with an A-B design. Data in this research was collected through audio documentation, photos, videos, and written documentation. The data was then analyzed using within-condition analysis and between-condition analysis. The research results show that the shaping Technique using tablet media effectively changes the behavior of autistic students who often grab other people's food. By using shaping techniques, autistic students can understand that snatching other people's food is not right and can control themselves not to do it. It shows that the use of behavior modification techniques using tablet media can help autistic students overcome unwanted behavior.